Norton Ginsburg, Bruce Koppel y T.G. Mcgee. The extended Metropolis, Settlement Transition in Asia. Honolulu: University of Hawaii Press, 1991, 339 pp. - Connelly, Marisela (Estudios de Asia y África, 1993)
-